Strategi Dinas Perindustrian dan Perdagangan Kota Tangerang Selatan dalam Penertiban Pedagang Kaki Lima di Pasar Ciputat Pascarevitalisasi - Nida Amalia; Muhammad Khoirul Anwar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2026)
The regulation of street vendors (PKL) at Ciputat Market following its revitalization indicates that efforts to reorganize public spaces in South Tangerang City still face challenges, particularly as street vendors continue to sell on the streets and sidewalks despite the availability of the revitalized market building. This has resulted in low occupancy rates. This study aims to identify and analyze the strategies employed by the South Tangerang City Industry and Trade Office in regulating street vendors at Ciputat Market following the revitalization, using Geoff Mulgan’s (2009) theoretical framework on government strategy as the analytical tool. The method used is descriptive with a qualitative approach. Data collection techniques included interviews, observations, and documentation. The research results indicate that the objective indicators have been formulated clearly and purposefully. Environmental indicators are supported by relatively adequate conditions and resources, although they have not yet been fully optimized strategically. The steering indicators demonstrate effective coordination across Regional Government Agencies (OPDs) through clear instructions and task allocation. Regarding the action indicators, enforcement efforts have successfully improved the physical order of the area, but this has not yet been followed by the optimization of economic activities within the market. Meanwhile, the learning indicators show that evaluation processes have been conducted, but they have not yet been systematically institutionalized and are not fully based on feedback from vendors.